Applying fuzzy logic systems in the estimation of crossflow filtration processes - da Silva, I. N.; Razuk, P. C.; Flauzino, R. A. (Institute of Electrical and Electronics Engineers (IEEE), 2001)
The crossflow filtration process differs of the conventional filtration by presenting the circulation flow tangentially to the filtration surface. The conventional mathematical models used to represent the process have some limitations in relation to the identification and generalization of the system behavior. In this paper, a system based on fuzzy logic systems is developed to overcome the problems usually found in the conventional mathematical models. Imprecisions and uncertainties associated with the measurements made on the system are automatically incorporated in the fuzzy approach. Simulation results are presented to justify the validity of the proposed approach.